Esensi Dan Urgensi Pengeluaran Pemerintah Untuk Pembangunan Daerah - Luciana L. Nahumuri (Institut Pemerintahan Dalam Negeri, 2019)
The essence and urgency of government expenditure for regional development is very crucial in realizing sustainable development, meaning that government spending must meet current needs without compromising the fulfillment of the needs of future generations. The higher the state revenue, the higher the state expenditure for regional development. Thus, an increase in understanding of government expenditure for regional development in a sustainable manner must be carried out with the principle of prudence in this country.